Liberal Education in Relation to Civic and Moral Education - Beata Maria Nosek (Nicolaus Copernicus University in Toruń, 2014)
This article is an attempt to find relationships that exist between liberal education, and civic and moral education. In a first few parts, the author defines the three types of education, presents their key assumptions, methods of implementation and the effects that should be achieved. Subsequently, the author tries to notice the relationships that connect them, and find points in common between them. Finding dependencies not only concerns those that connect liberal education with moral and civic education, but also those that exist between moral and civic education. The article ends with a summary, which is a commentary of the author on the issues discussed throughout the paper.